READINESS ASSESSMENT FOR IMPLEMENTATION OF INDUCTION STOVE’s INDONESIAN NATIONAL STANDARDIZATION (SNI) - Assahda, Talitha Nabila; Damayanti, Retno Wulan; Fahma, Fakhrina; Laksono, Pringgo Widyo; Setiadi, Haryono (JURNAL STANDARDISASI, 2024)
The Indonesian government has set a target to achieve net zero emissions (NZE) by 2060, part of which involves converting gas stoves to induction stoves for 8.2 million households by 2025. This initiative not only aims to reduce carbon emissions but also to decrease reliance on imported Liquefied Petroleum Gas (LPG), easing the strain on the state budget due to LPG subsidies. Standardizing induction stoves is crucial to ensure product quality and user safety. While Indonesia has existing standards for electric cooking equipment, specific standards for induction stoves are lacking, necessitating the development of Indonesian National Standards (SNI). To prepare for the implementation of these standards, a study focusing on the readiness of institutions involved in SNI implementation was conducted. Using the technoware, humanware, infoware, orgaware, cysnetware, manageware, and partnerware (THIOCMP) model, the study assessed the readiness of stakeholders. Thirty expert respondents participated in questionnaires and Focus Group Discussions (FGD). The findings indicate a high level of readiness among stakeholders, although improvements are needed in the orgaware component to ensure sustainable implementation of SNI for induction stoves. This research underscores the importance of thorough preparation for the successful adoption of new standards in Indonesia's transition to sustainable energy practices.